2009
DOI: 10.5194/aab-52-497-2009
|View full text |Cite
|
Sign up to set email alerts
|

Performance traits of purebred Ossimi and Rahmani lambs and their crosses with Finnsheep born under two accelerated mating systems

Abstract: Abstract. The aim of the study was to carry out crossing of the local breeds with a known prolific breed with the hope to be a beginning to develop improved synthetic lines under the sub-tropical conditions. In the present study, the data represented 4 genotypes: 2 pure Egyptian local fat-tailed breeds [Ossimi (O) and Rahmani (R)], one back-cross [1/4 Finnish Landrace (F) 3/4 O] and one 3-breed-cross [1/4 F 1/4 O 1/2 R]. The lambs resulted from two accelerated systems: 3 lambings/2 years and 2 lambings/1 year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…Present results indicated that Ossimi sheep have the largest value of live body weight (45.25 ± 1.98 Kg) at the third age category, and there weren't any significant differences between Rahmani and Barki breeds. The results of this study are in harmony with those previously reported by Almahdy et al (2000), Marai et al (2009), Khalifa et al (2013), Hassan (2017) and El-Malky et al (2019). They mentioned that the average live body weights were ranged from (51-53 kg) adult weight for the Ossimi and Rahmani breeds, and (44 kg) for the Barki breed.…”
Section: Growth Traitssupporting
confidence: 92%
See 1 more Smart Citation
“…Present results indicated that Ossimi sheep have the largest value of live body weight (45.25 ± 1.98 Kg) at the third age category, and there weren't any significant differences between Rahmani and Barki breeds. The results of this study are in harmony with those previously reported by Almahdy et al (2000), Marai et al (2009), Khalifa et al (2013), Hassan (2017) and El-Malky et al (2019). They mentioned that the average live body weights were ranged from (51-53 kg) adult weight for the Ossimi and Rahmani breeds, and (44 kg) for the Barki breed.…”
Section: Growth Traitssupporting
confidence: 92%
“…Another agreement obtained by Khalifa et al (2013) they found a positive effect of advanced age for Rahmani males live body weight. Furthermore, Marai et al (2009) and El-Malky et al (2019) reported that breed had a significant (P<0.01) effect on live body weight as Ossimi breed showed heavier weight than Rahmani and Barki breed.Another point of view reported by El-Tarabany et al (2017) they mentioned that there was no difference in live body weight between Ossimi and Rahmani breeds; however, Rahmani breed had a higher body weight compared to Ossimi breed. Body length differs according to many factors such as breed, gender, yield type, and age.…”
Section: Growth Traitsmentioning
confidence: 97%
“…According to the results of nucleotide sequencing for GDF-9 gene and SSCP technique for BMP-15 gene, Rahmani breed and its cross with Barki carried the mutations Fec-G H of GDF-9 and Fec-X G of BMP-15 genes. Additionally, the replacement of amino acids for GDF9 may enhance the high rate of twinning [18,26]. This theory agrees with our results on the twinning rate in Rahmani and its cross with Barki compared to other breeds.…”
Section: The Relationship Between Fertility and The Prevalence Of Bmpsupporting
confidence: 91%
“…Thus, the e ciency of meat production is higher than that of fat in intensive and semi-intensive sheep industry systems, and the tail fat of Altay sheep (comprising up to ~ 25% of carcass weight) markedly lowers their economic value [8]. For the above reasons, fat-tailed sheep breeds have been gradually rejected by producers and consumers, and leaner sheep breeds are more desirable [9][10][11][12][13][14]. Therefore, elucidation of the key genes that regulate the deposition and decomposition of tail fat in sheep and the molecular mechanisms controlling fat metabolism should greatly accelerate the breeding course of lean sheep and production of more healthy mutton for consumption.…”
Section: Introductionmentioning
confidence: 99%